Pediatric Acute Kidney Injury to the Subsequent CKD Transition - Fang Wang; Jie Ding (Karger Publishers, 2020)
Background: Both acute kidney injury (AKI) and CKD are complex syndromes caused by multiple etiologies and presented with various degrees of severity. Studies on adults provide strong evidence that AKI is an independent risk factor for both the initiation and progression of CKD, and the severity, frequency, and duration of AKI are crucial factors in the subsequent development of CKD. However, without consensus definitions of AKI and CKD and long-term follow-up studies using predictive biomarkers, it is difficult to clarify the potential for transition from AKI to CKD in pediatric populations. The goal of this review is to describe the most recent studies in epidemiology of pediatric AKI and biomarkers aiding in the earlier detection of AKI and CKD. Summary: KDIGO criteria for AKI have been widely applied for pediatric AKI studies. AKI in critically ill and non-critically ill children is common. CKD is highly prevalent in pediatric AKI survivors. Compared with traditional biomarkers such as serum Cr, proteinuria, and estimated glomerular filtration rate, urinary biomarkers earlier identifying AKI may also detect CKD earlier, but additional studies are required to determine their clinical utility. Key Messages: The use of consensus AKI criteria has improved our understanding of pediatric AKI epidemiology, and an association between AKI and CKD in pediatric populations has been endorsed. However, further studies are needed to better answer a definitive causal relationship between pediatric AKI and the subsequent development of CKD.